2017
DOI: 10.1371/journal.pone.0172860
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and utilization of the partograph: A cross-sectional survey among obstetric care providers in urban referral public health institutions in northwest and southwest Cameroon

Abstract: BackgroundThe enormous challenge to maternal well-being with associated maternal wastages during labour has remained an unsurmountable problem in Cameroon which reflects the current high maternal mortality rate. Evidence abounds that cost-effective and affordable health interventions like the use of the partograph will contribute to curb the alarming number of intrapartum maternal deaths. However, little is known about the level of knowledge and utilization of this simple life-saving tool in the North–and Sout… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
27
6

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 14 publications
1
27
6
Order By: Relevance
“…The prevalence of partograph use in this study is higher than the study done in Rwanda [60] 41.22%, Cameroon [61] 32.4%), and Nigeria[62] 37.5%. The possible reason might be the Federal Ministry of Health has set targets and working for facility delivery coverage at 90% and to enable all health centers to use partograph, and to provide all BEmONC functions [63].…”
Section: Discussioncontrasting
confidence: 72%
“…The prevalence of partograph use in this study is higher than the study done in Rwanda [60] 41.22%, Cameroon [61] 32.4%), and Nigeria[62] 37.5%. The possible reason might be the Federal Ministry of Health has set targets and working for facility delivery coverage at 90% and to enable all health centers to use partograph, and to provide all BEmONC functions [63].…”
Section: Discussioncontrasting
confidence: 72%
“…Admittedly, the TBAs did not have the skill set to monitor foetal heart rate using the partograph or manage complicated deliveries following training. Several studies even in non-crisis settings have found the partograph as a low-adoption intervention, 35,36 but the factors influencing use in this study were perceived by midwives to be continuous access to SBA during operating hours. In this study, conflict limited the movement of non-local staff in evening hours or during acute moments that resulted in lack of staffing of SBAs at the health facilities.…”
Section: Discussionmentioning
confidence: 67%
“…This level of knowledge is quite lower than the knowledge reported by many authors among health professionals about components and uses of partograph from various other countries of low-resource settings. [ 15 16 17 18 19 20 21 22 23 ] Almost 38% of the SBAs had received training to use the partograph in the present study. This finding is comparable to the status of training reported by many other studies.…”
Section: Discussionmentioning
confidence: 78%
“…Wide variations in the context of routine use of partograph have been reported by many studies. [ 8 17 19 20 22 21 22 23 24 ]…”
Section: Discussionmentioning
confidence: 99%